2016
DOI: 10.1074/jbc.m116.723080
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-β1 Increases DNA Methyltransferase 1 and 3a Expression through Distinct Post-transcriptional Mechanisms in Lung Fibroblasts

Abstract: DNA methylation is a fundamental epigenetic mark that plays a critical role in differentiation and is mediated by the actions of DNA methyltransferases (DNMTs). TGF-β1 is one of the most potent inducers of fibroblast differentiation, and although many of its actions on fibroblasts are well described, the ability of TGF-β1 to modulate DNA methylation in mesenchymal cells is less clear. Here, we examine the ability of TGF-β1 to modulate the expression of various DNMTs in primary lung fibroblasts (CCL210). TGF-β1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 68 publications
2
18
0
Order By: Relevance
“…We found that inhibition of both PI3K and ERK1/2 attenuated PDGFBB‐induced repression of miR‐1281, with PI3K's effect being mediated by upregulation of DNMT1 expression (Figure D and E). These data complement the recent study that identified PI3K–protein kinase B as the key pathway that increased DNMT1 expression by protecting DNMT1 protein from degradation in lung fibroblasts . Our data also reveal that the PI3K–protein kinase B pathway transcriptionally regulates DNMT1 expression in other cell types, such as PASMCs.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We found that inhibition of both PI3K and ERK1/2 attenuated PDGFBB‐induced repression of miR‐1281, with PI3K's effect being mediated by upregulation of DNMT1 expression (Figure D and E). These data complement the recent study that identified PI3K–protein kinase B as the key pathway that increased DNMT1 expression by protecting DNMT1 protein from degradation in lung fibroblasts . Our data also reveal that the PI3K–protein kinase B pathway transcriptionally regulates DNMT1 expression in other cell types, such as PASMCs.…”
Section: Discussionsupporting
confidence: 90%
“…These data complement the recent study that identified PI3K-protein kinase B as the key pathway that increased DNMT1 expression by protecting DNMT1 protein from degradation in lung fibroblasts. 67 Our data also reveal that the PI3K-protein kinase B pathway transcriptionally regulates DNMT1 expression in other cell types, such as PASMCs. PI3K-protein kinase B and MEK1/2-ERK1/2 pathways are known to maintain multiple cross-talk points in a context-dependent way, and their coordinated signaling determines cell fate.…”
Section: Discussionsupporting
confidence: 61%
“…In addition, TGF‐β1 promoted the expression of DNMT1 and DNMT3A, especially DNMT3A, which suggests that TGF‐β1 plays a certain role in the regulation of EYA4 expression in ESCC. In other human malignancies, TGF‐β1 has also been found to affect transcription and expression of downstream target genes via the regulation of DNMT expression . In ovarian cancer cells, TGF‐β1 induced the expression of DNMT and led to extensive genomic hypermethylation, which influenced the transcription of EMT‐related genes and promoted the EMT process .…”
Section: Discussionmentioning
confidence: 99%
“…In other human malignancies, TGF-b1 has also been found to affect transcription and expression of downstream target genes via the regulation of DNMT expression. [35][36][37] In ovarian cancer cells, TGF-b1 induced the expression of DNMT and led to extensive genomic hypermethylation, which influenced the transcription of EMT-related genes and promoted the EMT process. 38 In hepatocellular carcinoma, TGF-b1 transformed HCC cells into cells with a spindle-shaped morphology, which was accompanied by hypermethylation of CDH1 and the methylation of its promoter.…”
Section: Discussionmentioning
confidence: 99%
“…The role of mTOR signaling in modulating DNMT1 expression in cells is controversial. The level of DNMT1 was higher after treatment of the hepatocellular carcinoma cell lines with an mTOR inhibitor, Torin-2, whereas the increase in DNMT1expression by TGF-β treatment was abolished in fibroblasts by FAK, PI3K, and mTOR inhibitors, including rapamycin 37 , 38 . It is possible that the effects of activating mTOR on DNMT1 expression are diverse with respect to the cell types and stimuli.…”
Section: Discussionmentioning
confidence: 96%